A multispecies approach to fish management in the North Sea.
As fish overexploitation becomes more and more of a concern, stakeholders are constantly looking for novel resource management strategies and more accurate forecasting techniques. The GADCAP project has made an important contribution by test-driving the multispecies approach to fisheries management in the Flemish Cap.
Keywords: Fish management